The predictors of pain extent in people living with HIV. (15th November 2020) - Sabin, Caroline A.; Harding, Richard; Bagkeris, Emmanouil; Geressu, Adam; Nkhoma, Kennedy; Post, Frank A.; Sachikonye, Memory; Boffito, Marta; Anderson, Jane; Mallon, Patrick W.G.; Williams, Ian; Vera, Jaime; et al.
Abstract : Objective: To investigate the prevalence of widespread pain among people with HIV (PWH) and describe associations with antiretroviral therapy (ART) and markers of HIV disease stage. Design: Cross-sectional analysis of cohort study in the United Kingdom and Ireland. Methods: Pain information was collected during the baseline visit (conducted from 2013 to 2015) through a self-completed manikin identifying pain at 15 sites from five body regions. Pain was classified as widespread if reported at at least four regions and at least seven sites, or regional otherwise. Chi-squared tests, Kruskal–Wallis tests and ordinal logistic regression were used to consider associations between pain extent and sociodemographic and HIV-related factors. Results: Among the 1207 participants (614 PWH ≥ 50 years, 330 PWH < 50 years, 263 HIV-negative controls ≥50 years), pain was most commonly reported at the upper (left: 28.9%, right: 28.0%) and lower (left: 25.7%; right: 24.5%) leg, upper (18.6%) and lower (29.7%) back and shoulders (left: 16.0%; right: 16.8%). Widespread pain was more commonly reported in PWH than in HIV-negative controls (PWH ≥ 50 years: 18.7%; PWH < 50 years: 12.7%; HIV-negative ≥50 years: 9.5%) with regional pain reported in 47.6, 44.8 and 49.8%, respectively (global P  = 0.001). In multivariable analyses, pain extent was greater in those with lower educational attainment, those exposed to more ART drugs, and those with a higher current CD4 + cell count but longer exposure to immunosuppression. Conclusion: Widespread pain is commonly reported in PWH and is associated with longer duration of exposure to HIV, immunosuppression and ART. Our findings call for greater awareness, and interventions to support the management, of pain in PWH.